Relativistic fluid dynamics : lectures given at the 1st 1987 session of the Centro internazionale matematico estivo (C.I.M.E.) held at Noto, Italy, May 25-June 3, 1987 - Anile, Angelo M; Choquet-Bruhat, Yvonne (C.I.M.E. Foundation Subseries, 1989)
In recent years the subject of relativistic fluid dynamics has found substantial applications in astrophysics and cosmology (theories of gravitational collapse, models of neutron stars, galaxy formation), as well as in plasma physics (relativistic fluids have been considered as models for relativistic particle beams) and nuclear physics.